Optimization of treaining process in pre-start fencing training on the base of out-of-training means' of mobilization orientation application - G.O. Lopatenko (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: to show effectiveness of out-of- training means of mobilization orientation in pre-start preparation of elite fencers. Material: in the research 12 elite sportsmen-fencers participated. Results: it was found that under influence of the worked out pre-start complex (during 15-18 minutes), comparing with traditional warming up (40 minutes) more expressed mobilization effect was registered. This effect also lasted longer time. Higher stimulating effects of pre-start complex are proved by confident differences in sportsmen's special workability (p -0.05). Conclusions: the achieved stimulating effects reduced duration of general warming up to twenty minutes. It permits to more rationally organize pre-start training of fencers in comparison with application of traditional means.